CITIZENSHIP FROM THE PRINCIPLE OF HUMAN RIGHTS (CASE STUDY OF SETIA WATTI S. LALANG IN BATAM CITY) - Ilham Bela Perkasa; Siti Nurkhotijah; Ramlan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Citizenship is a fundamental legal status that forms the basis for recognizing every individual's civil, political, social, and economic rights. However, in practice, legal and social issues still cause individuals to lose their citizenship status (involuntary statelessness) unintentionally. This study highlights the case of Setia Watti S. Lalang in Batam City as a concrete example of the failure of legal and administrative systems to ensure the protection of the right to citizenship per the principles of human rights. Setia Watti, a woman born in Indonesia who in practice lives as an Indonesian citizen, faces uncertainty regarding her legal status due to documentation issues and overlapping policies between various agencies. This study aims to analyze the legal regulation of citizenship in Indonesia from a juridical perspective, examine the law's implementation in such cases, and identify challenges and obstacles in resolving cases of loss of citizenship. The methods used are normative juridical and empirical juridical legal research methods with a statute approach and a socio-legal approach, as well as collecting primary data through interviews and field observations. The research results show a gap between positive legal norms, the administrative practices implemented by the relevant agencies, and a lack of coordination among institutions in handling cases of loss of citizenship. In addition, the legal approach that is not yet based on human rights further marginalizes vulnerable groups such as women and children from mixed marriages. This study recommends the need for affirmative policies, improvements to derivative regulations of the Citizenship Law, cross-sectoral synergy and active participation of civil society in advocating for the fulfillment of the right to citizenship.